Complications of orbital endoimplantation in the Eye Clinic of the Lithuanian University of Health Sciences - Piškinienė, Raimonda; Banevičius, Mantas (Acta medica Lituanica, 2017)
The aim of the study was to analyse the rate of complications of orbital endoimplantation in patients operated from 2002 to 2014 at the Eye Clinic of the Lithuanian University of Health Sciences and to compare it with the results in the literature. Enucleation must be performed very carefully in order to prevent any additional trauma, infection, deformation, and to create an optimal conjunctival socket. However, complications occur despite efforts and qualified surgeons. The most common complications described in the literature are thinning and cysts of the conjunctiva, a foreign body reaction, secretion, symblepharons, fornix deficiency, ptosis, permanent pain, dislocation, migration and protrusion of the  implant, a primary or secondary infection, and implant extrusion. From 2002 to 2014, 128 patients underwent orbital endoimplantation surgery at the  Eye Clinic. The  most common complications were conjunctival erosion (five patients, or 2.9%), cysts (nine patients, or 7%), and implant extrusion (five patients, or 2.9%). The type and rate of complications were very similar to the data in the literature.